Bistability of equilibria and the 2-tori dynamics in an endogenous growth model undergoing the cusp–Hopf singularity. (February 2018) - Bella, Giovanni; Mattana, Paolo
Abstract: This paper studies the properties of bistability of equilibria, giving rise to periodic oscillations and 2-tori chaotic dynamics in the full three-dimensional structure of the generalized version of the Chamley (1993) endogenous growth model. This complex dynamic phenomenon reflects a particular hopf bifurcation degeneracy that originates in the neighborhood of a so-called Gavrilov–Guckenheimer singularity, with asymptotical stability properties that lead to persistent oscillations under small perturbations, until a chaos frontier is reached. As a consequence, we study all the necessary conditions, and the exact parametric configuration, that allow to locate the economy on the optimal path that avoids this undesired long run indeterminate solution.